SELECTION FOR THE DEVELOPMENT OF BLACK EYE COWPEA LINES - JÉSSICA DANIELE LUSTOSA DA SILVA; KAESEL JACKSON DAMASCENO-SILVA; MAURISRAEL DE MOURA ROCHA; JOSÉ ÂNGELO NOGUEIRA DE MENEZES JÚNIOR; VALDENIR QUEIROZ RIBEIRO (Revista Caatinga, 2018)
Cowpea bean is a socioeconomically important legume that contribute to generate employment and income. This species presents great grain variability, and the commercial subclass black eye stands out as a very appreciated grain in Brazil and abroad, thus requiring the development of new cultivars. The objective of this work was to evaluate and select lineages of commercial black eye cowpea, based on simultaneous, and direct selection. First, 105 progenies and four controls were evaluated using the Federer's augmented block design. Seventy-seven progenies, selected from this evaluation-first selection cycle-and four controls were evaluated in three environments, using a simple 9×9 lattice design. Based on this evaluation, the second selection cycle was possible, resulting in 24 progenies. The gain by direct selection was lower than the predicted gain for grain yield in the first cycle, indicating that the selection was not effective. This result was probably due to the reduced genetic variability caused by the selection pressure. In the second cycle, the predicted and observed gains were similar, indicating that much of the expected gain was observed. The predicted and observed gains, with simultaneous selection based on the rank sum selection index, were similar in the first and second cycle. The simultaneous and direct selections resulted in genetic gains for grain yield in the two selection cycles, making it possible the selection of high grain yield lineages.